Comparison of Two Methods for the Extraction of Fractionated Rice Bran Protein - Changyuan Wang; Dan Li; Feng Xu; Tianshu Hao; Min Zhang (Journal of Chemistry)
Two different methods for extracting fractionated rice bran protein (FRBP) from defatted rice bran were investigated according to the solubility of protein in different extraction solvents. The yields of the obtained proteins and their purity were first compared. Sodium dodecyl sulfate polyacrylamide gel electrophoresis, differential scanning calorimetry, protein surface hydrophobicity, and protein secondary molecular structure analyses were subsequently applied to identify and compare the compositional, structural, and functional characteristics of the obtained proteins. The highest yield (13.8%, w/w) and purity (45–47%) of FRBP products were obtained using 0.4 M NaCl, 80% ethanol, and 0.01 M NaOH as extraction solvents to fractionate albumin, globulin, prolamin, and glutelin. Several good properties were exhibited, including good functionality, specific denaturation temperature, and enthalpy values, for FRBP products prepared by the above method.